2010
DOI: 10.1097/iop.0b013e3181bd436f
|View full text |Cite
|
Sign up to set email alerts
|

Isolated Optic Nerve Infiltration in Systemic Lymphoma—A Case Report and Review of Literature

Abstract: Ocular involvement in non-Hodgkin lymphoma occurs either as primary ocular, central nervous system lymphoma or isolated intraocular lymphoma. Recurrence of systemic non-Hodgkin lymphoma in the form of CNS lymphoma has been reported. However, recurrence as an isolated optic nerve lesion without involving CNS has never been reported in the pediatric age group. We report a case of systemic diffuse large B-cell lymphoma in a 2-year-old female, which primarily occurred as suprapubic mass and later recurred in the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 3 publications
0
18
0
Order By: Relevance
“…Isolated LON without other CNS involvement or systemic disease has been reported in the literature and can be either unilateral or bilateral [1][2][3][4][5]. Visual loss is usually severe and is frequently associated with disc swelling, peripapillary haemorrhage and RAPD.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Isolated LON without other CNS involvement or systemic disease has been reported in the literature and can be either unilateral or bilateral [1][2][3][4][5]. Visual loss is usually severe and is frequently associated with disc swelling, peripapillary haemorrhage and RAPD.…”
Section: Discussionmentioning
confidence: 93%
“…Treatment with high dose prednisone only leads to temporary improvement of VA [6]. Combined retinal vein and artery occlusions due to infiltration of the lymphoblastic cells are also well recognised [1][2][3].…”
Section: Discussionmentioning
confidence: 94%
“…Kim et al have reported a case of infiltrative optic neuropathy occurring as the sole manifestation of disease recurrence in a patient with systemic NHL otherwise thought to be in clinical remission 6. Besien et al studied the treatment of CNS recurrence in patients with NHL, and showed that intrathecal chemotherapy treatment did not result in meaningful responses while radiation therapy frequently resulted in transient, symptomatic relief 7.…”
Section: Discussionmentioning
confidence: 99%
“…However, an intraocular lymphoma secondary to systemic lymphoma is not common and is usually limited to the uveal tract [5,9]. There are several reports of the optic nerve involvement in cases of systemic NHL [10][11][12]. Several cases of infiltrative optic neuropathy have also been reported which may be the first manifestation of a recurrence of the NHL [11,13].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, no lymphocytes were found the CSF. In earlier cases, most patients who had the optic nerve involvement with systemic diseases had positive neuroimaging with enhancement of the optic nerve or positivity for malignant cells in the CSF [10][11][12]16].…”
Section: Citation: Furuya N Oshitari T Sato E Baba T Yamamoto S (mentioning
confidence: 99%